Method for evaluating positive electrode slurry of all-solid-state battery
The method uses AC impedance measurement to evaluate the coating state of the solid electrolyte in all-solid-state battery slurries, addressing the accuracy issue and enhancing battery performance and manufacturing control.
Patent Information
- Application Number
- JP2023094676
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-08
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2043-06-08
AI Technical Summary
Existing methods fail to accurately evaluate the coating state of the solid electrolyte in the positive electrode active material of all-solid-state batteries, which affects battery performance and quality control during manufacturing.
A method involving AC impedance measurement of a positive electrode slurry containing a solid electrolyte, conductive aid, and binder material, using parameters from the AC impedance imaginary and real axes to evaluate the coating state of the solid electrolyte in the positive electrode active material.
Enables accurate evaluation of the solid electrolyte coating state, stabilizing battery performance and improving quality control in the manufacturing process.
Smart Images

Figure 2024176250000001 
Figure 2024176250000002 
Figure 2024176250000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for accurately evaluating the quality of a positive electrode slurry containing an active material, a solid electrolyte, a conductive assistant, a binder material, etc. for an all-solid-state battery in a slurry state. [Background technology]
[0002] In the manufacture of electrode slurries for use in liquid electrolyte lithium ion batteries and all-solid-state lithium ion batteries, the quality of the electrode slurries is generally controlled by rheological evaluation such as viscosity. As a method for controlling the quality of the electrode slurries, for example, a technique is known in which the electrode slurries are sampled immediately after manufacture and the AC impedance of the electrode slurries is measured to determine the quality of the electrode slurries. As a method for evaluating the quality of the positive electrode slurries of all-solid-state lithium ion batteries, for example, a method is given in which the coating state of the coating material on the electrode active material is evaluated.
[0003] Patent Document 1 describes a method for producing a paste containing an active material, a solid electrolyte, and a conductive additive, comprising: a measurement step of measuring the AC impedance of the paste corresponding to a predetermined measurement frequency band; a composition ratio determination step of determining whether or not a composition ratio of the paste is outside a predetermined range based on a width in the real part direction of an arc portion corresponding to the predetermined frequency band in a locus drawn on a complex impedance plane by the measured AC impedance; and a removal step of removing paste whose composition ratio is determined to be outside the predetermined range.
[0004] Patent Document 2 describes a paste evaluation method for evaluating a paste to be applied to an electrode surface of a battery, which uses a container having a rotation mechanism and a measurement unit that measures the AC impedance of the paste, and describes how the paste contained in the container is rotated by the rotation mechanism while the measurement unit measures the AC impedance of the paste, and how the measurement unit has a pair of application electrode plates arranged in parallel to apply an AC voltage to the paste, and how the measured values of the AC impedance for one or more rotations by the rotation mechanism are averaged to correct measurement errors arising from parallelism errors of the pair of application electrode plates. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-222651 A [Patent Document 2] Patent No. 5505318 Summary of the Invention [Problem to be solved by the invention]
[0006] Compared to liquid electrolyte lithium-ion batteries, cathode slurries for all-solid-state batteries use more materials and contain a composite element of active material and solid electrolyte, and it is believed that the composite (coating state) of the solid electrolyte on the cathode active material contributes greatly to battery performance. However, no specific method has been found to evaluate the coating state of the solid electrolyte on the cathode active material in a slurry state, making it difficult to accurately evaluate the coating state.
[0007] In order to solve the above problems, the present application aims to accurately evaluate the coating state of a solid electrolyte in a positive electrode active material in a positive electrode slurry for an all-solid-state battery, thereby contributing to stabilization of battery performance, improvement of quality control in the manufacturing process, and ultimately energy efficiency. [Means for solving the problem]
[0008] [1] A measurement step of sealing a positive electrode slurry for an all-solid-state battery, in which a positive electrode active material, a solid electrolyte, a conductive assistant, and a binder material are kneaded and dispersed, in a measurement container provided with electrodes on both ends, and measuring AC impedance; a frequency domain identification step of identifying a frequency domain from the AC impedance data; and an evaluation step of evaluating whether a coating state of the solid electrolyte on the positive electrode active material is good or bad, based on a parameter on an AC impedance imaginary axis of the specified frequency region and a parameter on an AC impedance real axis of the specified frequency region.
[0009] The method for evaluating a positive electrode slurry for an all-solid-state battery of the present invention can accurately evaluate the coating state of a solid electrolyte in a positive electrode active material from the measured AC impedance of the positive electrode slurry for an all-solid-state battery, based on a parameter on the imaginary axis of the AC impedance in a specific frequency region and a parameter on the real axis of the AC impedance in a specific frequency region.
[0010] [2] The method for evaluating a positive electrode slurry for an all-solid-state battery according to [1], wherein the parameter on an imaginary axis of the AC impedance is an imaginary component (Zim) of the AC impedance of the positive electrode slurry for the all-solid-state battery, or a polarization charge (Cp) derived from the imaginary component (Zim) of the AC impedance.
[0011] The evaluation method for a positive electrode slurry for an all-solid-state battery of the present invention uses the imaginary component of AC impedance (Zim) or the polarization charge (Cp) derived from the imaginary component of AC impedance (Zim) as a parameter on the imaginary axis of AC impedance, and therefore can accurately evaluate the coating state of the solid electrolyte on the positive electrode active material.
[0012] [3] The method for evaluating a positive electrode slurry for an all-solid-state battery according to [1] or [2], wherein the parameter of the real axis of the AC impedance is a real component (Zre) of the AC impedance of the positive electrode slurry for the all-solid-state battery.
[0013] The evaluation method for a positive electrode slurry for an all-solid-state battery of the present invention uses the real component (Zre) of the AC impedance of the positive electrode slurry for an all-solid-state battery as a parameter of the real axis of the AC impedance, and therefore can accurately evaluate the dispersion state of the positive electrode slurry.
[0014] [4] The method for evaluating a positive electrode slurry for an all-solid-state battery according to any one of [1] to [3], wherein in the frequency range specifying step, the AC impedance of the positive electrode slurry for the all-solid-state battery is evaluated in two or more frequency ranges.
[0015] The method for evaluating a positive electrode slurry for an all-solid-state battery of the present invention evaluates the AC impedance of the positive electrode slurry for an all-solid-state battery in two or more frequency ranges, and therefore can accurately evaluate the coating state of the solid electrolyte on the positive electrode active material.
[0016] [5] The method for evaluating a positive electrode slurry for an all-solid-state battery according to any one of [1] to [4], wherein in the frequency domain identification step, a polarization charge (Cp) derived from an imaginary component (Zim) of the AC impedance and a real component (Zre) of the AC impedance obtained in different frequency domains are evaluated for quality either alone or in combination.
[0017] The evaluation method for a positive electrode slurry for an all-solid-state battery of the present invention evaluates the AC impedance of the positive electrode slurry for an all-solid-state battery by combining a parameter on the imaginary axis of the AC impedance obtained by dividing the AC impedance of the positive electrode slurry into two or more frequency regions and a parameter on the real axis of the AC impedance, so that the coating state of the solid electrolyte in the positive electrode active material can be evaluated with higher accuracy. Effect of the Invention
[0018] According to the present invention, in a positive electrode slurry for an all-solid-state battery, the coating state of a positive electrode active material with a solid electrolyte can be evaluated with high accuracy. [Brief description of the drawings]
[0019] [Figure 1] 1 is a flowchart showing a method for evaluating a positive electrode slurry for an all-solid-state battery according to the present embodiment. [Diagram 2] FIG. 2 is a diagram showing an example of a Nyquist plot showing the measurement result of the AC impedance of a positive electrode slurry for an all-solid-state battery. [Diagram 3] FIG. 2 is a graph showing the relationship between the load strength and the polarization charge (Cp) in the solid electrolyte coating step of the all-solid-state battery active material in Example 1. [Figure 4] FIG. 2 is a diagram showing the relationship between load strength and real component (Zre) in a solid electrolyte coating step of an active material for an all-solid-state battery in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present invention will be described in detail.
[0021] [Evaluation method of positive electrode slurry for all-solid-state batteries] A method for evaluating a positive electrode slurry for an all-solid-state battery according to an embodiment of the present invention includes a measurement step of enclosing a positive electrode slurry for an all-solid-state battery, in which a positive electrode active material, a solid electrolyte, a conductive assistant, and a binder material are kneaded and dispersed, in a measurement container provided with electrodes on both ends, and measuring AC impedance, a frequency domain identification step of identifying a frequency domain from the AC impedance data, and an evaluation step of evaluating the quality of a coating state of the solid electrolyte on the positive electrode active material, based on a parameter on the AC impedance imaginary axis of the identified frequency domain and a parameter on the AC impedance real axis of the identified frequency domain.
[0022] The method for evaluating a positive electrode slurry for an all-solid-state battery of this embodiment may include a step of preparing a positive electrode slurry for an all-solid-state battery to be evaluated by the method for evaluating a positive electrode slurry for an all-solid-state battery of this embodiment.
[0023] FIG. 1 is a flowchart showing a method for evaluating a positive electrode slurry for an all-solid-state battery according to this embodiment.
[0024] "Preparation process" In the method for evaluating a positive electrode slurry for an all-solid-state battery according to this embodiment, the positive electrode slurry for an all-solid-state battery prepared in the preparation step (S1 shown in FIG. 1) is evaluated. The all-solid-state battery positive electrode slurry that is the subject of quality control by the evaluation method for the all-solid-state battery positive electrode slurry of this embodiment contains a positive electrode active material, a solid electrolyte, a conductive assistant, and a binder material.
[0025] The positive electrode active material is not particularly limited as long as it can reversibly release and absorb lithium ions and transport electrons, and any known positive electrode active material that can be applied to the positive electrode of an all-solid-state lithium ion battery can be used. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), solid solution oxide (Li2MnO3-LiMO2 (M=Co, Ni, etc.)), lithium manganese nickel cobalt oxide (LiNi x Mn y Co z O2, x+y+z=1), composite oxides such as olivine-type lithium phosphate (LiFePO4), conductive polymers such as polyaniline and polypyrrole, sulfides such as Li2S, CuS, Li-Cu-S compounds, TiS2, FeS, MoS2, and Li-Mo-S compounds, mixtures of sulfur and carbon, etc. The positive electrode active material may be composed of one kind of the above materials alone, or may be composed of two or more kinds.
[0026] The solid electrolyte is not particularly limited as long as it has lithium ion conductivity and insulation, and materials generally used in all-solid-state lithium ion batteries can be used. For example, inorganic solid electrolytes such as sulfide solid electrolyte materials, oxide solid electrolyte materials, halide solid electrolytes, and lithium-containing salts, polymer-based solid electrolytes such as polyethylene oxide, and gel-based solid electrolytes containing lithium-containing salts and lithium ion conductive ionic liquids can be mentioned. Among these, sulfide solid electrolyte materials are preferable from the viewpoint of high lithium ion conductivity and good structural formability and interface bonding properties by pressing. The form of the solid electrolyte material is not particularly limited, but may be, for example, in the form of particles.
[0027] The positive electrode slurry for all-solid-state batteries may contain a conductive assistant from the viewpoint of improving the conductivity of the positive electrode. As the conductive assistant, a conductive assistant that can be generally used in all-solid-state lithium-ion batteries can be used. For example, carbon black such as acetylene black and ketjen black; carbon fiber; vapor-grown carbon fiber; graphite powder; carbon materials such as carbon nanotubes can be mentioned. The conductive assistant may be composed of one kind of the above materials alone or two or more kinds.
[0028] The positive electrode slurry for the all-solid-state battery may contain a solvent from the viewpoint of adjusting the viscosity.
[0029] The positive electrode slurry for an all-solid-state battery can be prepared by blending a positive electrode active material, a solid electrolyte, a conductive assistant, and a binder material in a predetermined blending ratio, and kneading the mixture containing the positive electrode active material, the solid electrolyte, the conductive assistant, and the binder material in a kneader.
[0030] "Measurement process" In the measurement step, the positive electrode slurry for the all-solid-state battery is placed between two electrodes, and an AC voltage or an AC current is applied between the two electrodes to measure the AC impedance of the positive electrode slurry for the all-solid-state battery (S2 shown in FIG. 1). In the method for evaluating a positive electrode slurry for an all-solid-state battery of this embodiment, the frequency of the AC voltage or AC current used to measure the AC impedance of the positive electrode slurry for an all-solid-state battery is continuously changed from 5 MHz to 1 Hz, for example.
[0031] "Frequency domain identification process" In the frequency range identifying step, an AC frequency range used for evaluating the coating state of the solid electrolyte on the positive electrode active material is identified from the measurement data of the AC impedance acquired in the measuring step (S3 shown in FIG. 1). In the method for evaluating the coating state of the solid electrolyte in the positive electrode active material of the present invention, the coating state can be evaluated with high accuracy by using the parameters of the AC impedance imaginary axis in a specific frequency range and the parameters of the AC impedance real axis in a specific frequency range among the AC impedance measurement data obtained in the measurement step. For example, 5 kHz to 50 kHz, 100 Hz to 1 kHz, 5 Hz to 20 Hz, etc. are selected as the AC frequency range used for evaluating the coating state.
[0032] The parameter of the imaginary axis of the AC impedance of the positive electrode slurry for the all-solid-state battery is preferably the imaginary component of the AC impedance (Zim) or the polarization charge (Cp) derived from the imaginary component of the AC impedance (Zim). A method for specifying the frequency domain of the imaginary component (Zim) or the polarization charge (Cp) used for evaluating the coating state will be described. The imaginary component (Zim) of the AC impedance or the polarization charge (Cp) derived from the imaginary component (Zim) of the AC impedance in the AC frequency range between 5 Hz and 20 Hz is set as the imaginary axis parameter used for evaluating the coating state, at a frequency at which the imaginary component (Zim) or the polarization charge (Cp) changes most significantly depending on the type of the positive electrode slurry for an all-solid-state battery to be measured. The frequency at which this imaginary axis parameter changes most significantly varies depending on the material of the active material, etc., but for example, the frequency at which the imaginary axis parameter changes most significantly can be identified by evaluating a sample in which the load intensity of the solid electrolyte coating process of the active material for an all-solid-state battery is changed. In the case of the positive electrode slurry for an all-solid-state battery in the embodiment, the frequency at which the imaginary component (Zim) or the polarization charge (Cp) changes most significantly is, for example, 10 Hz.
[0033] The parameter of the real axis of the AC impedance of the positive electrode slurry for the all-solid-state battery is preferably the real component (Zre) of the AC impedance of the positive electrode slurry for the all-solid-state battery. A method for specifying the frequency domain of the real component (Zre) used for evaluating the coating state will be described. The data of the AC impedance obtained in the measurement step is divided into a real component (Zre) on the horizontal axis and an imaginary component (Zim) on the vertical axis and displayed on a complex plane (Nyquist plot). FIG. 2 is a diagram showing an example of a Nyquist plot of the AC impedance measurement of the positive electrode slurry for an all-solid-state battery obtained in the measurement step. As shown in FIG. 2, the Nyquist plot of the positive electrode slurry for an all-solid-state battery theoretically has three arcs. However, it is difficult to obtain the first arc in the real part direction with the measuring equipment currently in general use. In FIG. 2, the frequency of the boundary between the second arc in the real part direction from the low impedance side and the third arc is set as the frequency of the real component (Zre) used to evaluate the coating state. The second arc portion corresponds to a frequency range from 1 kHz to 1 MHz, and the third arc portion corresponds to a frequency range from 5 Hz to 1 kHz.
[0034] "Step of evaluating the coating state of solid electrolyte on positive electrode active material" In the evaluation step of the coating state of the solid electrolyte on the positive electrode active material (hereinafter, the evaluation step), the coating state of the solid electrolyte on the positive electrode active material is evaluated based on the parameter of the AC impedance imaginary axis and the parameter of the AC impedance real axis at the frequency specified in the frequency range specifying step, from among the AC impedance measurement results of the all-solid-state battery positive electrode slurry obtained in the measurement step (S4 in FIG. 1).
[0035] When the parameter of the AC impedance imaginary axis in the frequency region specified in the frequency region specifying step satisfies a reference value previously set from the AC impedance measurement result of an all-solid-state battery positive electrode slurry (hereinafter, good slurry) having a good solid electrolyte coating state in the positive electrode active material, and the parameter of the AC impedance real axis in the frequency region specified in the frequency region specifying step satisfies a reference value previously set from the AC impedance measurement result of the good slurry, the positive electrode slurry is judged to be an all-solid-state battery positive electrode slurry having a good solid electrolyte coating state in the positive electrode active material. The reference value is determined from the AC impedance measurement result of the slurry judged to be a good slurry, based on, for example, the battery performance, the dispersion state of the slurry obtained using an analytical method such as a particle size distribution meter, the coating thickness of the solid electrolyte calculated using an analytical method such as an electron microscope, etc. The upper limit and lower limit of the reference value are determined according to the type of the positive electrode slurry for the all-solid-state battery.
[0036] When the parameter of the imaginary axis of the AC impedance in the frequency region specified in the frequency region specifying step does not satisfy a preset reference value based on the AC impedance measurement result of a good-quality slurry, or when the parameter of the real axis of the AC impedance in the frequency region specified in the frequency region specifying step does not satisfy a preset reference value based on the AC impedance measurement result of a good-quality slurry, the slurry is determined to be a positive electrode slurry for an all-solid-state battery in which the coating state of the solid electrolyte in the positive electrode active material is poor.
[0037] According to the method for evaluating a positive electrode slurry for an all-solid-state battery of this embodiment, the AC impedance of the positive electrode slurry for an all-solid-state battery is measured in a specific frequency range, and the coating state of the solid electrolyte in the positive electrode active material can be evaluated with high accuracy based on the obtained parameters on the imaginary axis of the AC impedance and the parameters on the real axis of the AC impedance. EXAMPLES
[0038] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0039] [Example 1] "Preparation of cathode slurry for all-solid-state batteries" In advance, in order to change the coating state of the positive electrode active material, composite materials were prepared by changing the processing conditions in four patterns in the solid electrolyte coating process. The four patterns were prepared under conditions with low to high processing loads. Thereafter, a positive electrode slurry for an all-solid-state battery was prepared as shown below. The binder solution and the conductive assistant dispersion were mixed by stirring at 2000 rpm for 1 minute using a planetary centrifugal mixer (kneading device), and mixture 1 was obtained. To the obtained mixture 1, zirconia balls with a diameter of 2 mm, a positive electrode active material (already coated with a solid electrolyte, for example, positive electrode active material:solid electrolyte=75:25 to 90:10 (mass ratio)), and a solvent (butyl butyrate) were added and stirred at 2000 rpm for 1 minute to obtain mixture 2. To the obtained mixture 2, a solid electrolyte and a solvent (butyl butyrate) were added, and the mixture was kneaded for 1 minute at 2000 rpm using a kneading device, to obtain a mixture 3. To the obtained mixture 3, a dilution solvent (butyl butyrate) was added, and the mixture was stirred and mixed at 2000 rpm for 2 minutes to obtain a mixture 4. Thereafter, a step of kneading while repeatedly diluting was carried out.
[0040] "Impedance Measurement: Imaginary Component (Cp)" The AC impedance of the positive electrode slurry for solid-state batteries obtained by changing each processing condition was measured, and the polarization charge (Cp) derived from the parameter (Zim) of the imaginary axis of the AC impedance was calculated to investigate the relationship between the load strength conditions in the coating process and the polarization charge (Cp). The results are shown in Figure 3. From the results shown in Figure 3, it was found that the load strength and the polarization charge (Cp) show a proportional relationship, and the greater the load strength, the smaller the polarization charge (Cp). This indicates that the greater the load strength, the more the active material is coated with the solid electrolyte, and the smaller the surface area of the exposed positive electrode active material becomes, and the better the particle state is with the solid electrolyte.
[0041] "Impedance measurement: real component (Zre)" The real component (Zre) of the AC impedance of the positive electrode slurry for all-solid-state batteries was calculated as a parameter of the real axis of the obtained AC impedance, and the relationship between the processing conditions of the positive electrode slurry for all-solid-state batteries and the real component (Zre) was investigated. The results are shown in Figure 4. From the results shown in Figure 4, it was found that the load intensity and the real component (Zre) show a proportional relationship, and the larger the load intensity, the larger the real component (Zre). From other verification results, it is presumed that there is no direct causal relationship with the coating state of the solid electrolyte. However, it is presumed that the dispersion state is different in the all-solid slurry with different processing conditions, and that the difference in the dispersion state is shown, and if the real axis parameter is within a preset reference value, it can be judged that the dispersion state is good.
[0042] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to the above-described embodiments, and various modifications and variations are possible within the scope of the gist of the present invention as described in the claims.
Claims
1. a measuring step of sealing the positive electrode slurry for an all-solid-state battery, in which a positive electrode active material, a solid electrolyte, a conductive assistant, and a binder material are kneaded and dispersed, in a measuring container provided with electrodes on both ends, and measuring the AC impedance; a frequency domain identification step of identifying a frequency domain from the AC impedance data; and an evaluation step of evaluating whether a coating state of the solid electrolyte on the positive electrode active material is good or bad, based on a parameter on an AC impedance imaginary axis of the specified frequency region and a parameter on an AC impedance real axis of the specified frequency region.
2. 2. The method for evaluating a positive electrode slurry for an all-solid-state battery according to claim 1, wherein the parameter on the imaginary axis of the AC impedance is an imaginary component (Zim) of the AC impedance of the positive electrode slurry for an all-solid-state battery, or a polarization charge (Cp) derived from the imaginary component (Zim).
3. 2. The method for evaluating a positive electrode slurry for an all-solid-state battery according to claim 1, wherein the parameter on the real axis of the AC impedance is a real component (Zre) of the AC impedance of the positive electrode slurry for an all-solid-state battery.
4. The method for evaluating a positive electrode slurry for an all-solid-state battery according to claim 1 , wherein in the frequency range specifying step, the AC impedance of the positive electrode slurry for an all-solid-state battery is evaluated in two or more frequency ranges.
5. 2. The method for evaluating a positive electrode slurry for an all-solid-state battery according to claim 1, wherein in the frequency region specifying step, a polarization charge (Cp) derived from an imaginary component (Zim) of the AC impedance and a real component (Zre) of the AC impedance obtained in different frequency regions are evaluated as good or bad either alone or in combination.
Citation Information
Patent Citations
Positive electrode slurry for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery with positive electrode manufactured using it
JP2005259512A
Positive electrode composite active material, lithium ion secondary battery, and production method for lithium ion secondary battery
WO2023063303A1
Gelled article filling container
JP1980005318A
Method for producing paste
JP2015222651A
